LncRNA AC010789.1 Promotes Colorectal Cancer Progression by Targeting MicroRNA-432-3p/ZEB1 Axis and the Wnt/β-Catenin Signaling Pathway - Duan, Weili; Kong, Xue; Li, Juan; Li, Peilong; Zhao, Yinghui; Liu, Tong; Binang, Helen Barong; Wang, Yunshan; Du, Lutao; Wang, Chuanxin (Frontiers in Cell and Developmental Biology, 2020)
Accumulating literatures have indicated that long non-coding RNAs (lncRNAs) are crucial molecules in tumor progression in various human cancers, including colorectal cancer (CRC). However, the clinical significance and regulatory mechanism of a vast majority of lncRNAs in CRC remains to be determined. The current study aimed to explore the function and molecular mechanism of lncRNA AC010789.1 (AC010789.1) in CRC progression. AC010789.1 was found to be overexpressed in CRC tissues and cells. High expression of AC010789.1 was associated with lymph node metastasis and poor prognosis. Moreover, AC010789.1 silencing inhibited proliferation, migration, invasion and epithelial-mesenchymal transition (EMT) in vitro as well as tumorigenesis and metastasis in vivo. Mechanistically, we demonstrated that repression of AC010789.1 promoted miR-432-3p expression and miR-432-3p directly binds to ZEB1. We then proved the anti-tumor role of miR-432-3p in CRC, showing that the inhibitory effect of AC010789.1 knockdown on CRC cells was achieved by upregulation of miR-432-3p but downregulation of ZEB1. We also established that silencing AC010789.1 suppressed the Wnt/β-catenin signaling pathway, but this inhibitory effect was partially counteracted by inhibition of miR-432-3p. In summary, these results reveal that silencing AC010789.1 suppresses CRC progression via miR-432-3p-mediated ZEB1 downregulation and suppression of the Wnt/β-catenin signaling pathway, highlighting a potentially promising strategy for CRC treatment.LncRNA AC010789.1/miR-432-3p/ZEB1 axis in CRC